Can we identify the neglected/emotional abused preschool child? A systematic review. (4th April 2011) - Naughton, A; Mann, M; Tempest, V; Kemp, A M; Maguire, S
Abstract : Aims: Early neglect has far reaching consequences for a child's emotional, psychological and social development. Professionals lack confidence in identifying the thresholds for action in such cases, and our systematic review aims to define the evidence base for recognising such children. Methods: Using 160 key words & phrases we searched 18 databases and four websites (1960–2009), supplemented by handsearching journals and references. Of 7018 abstracts identified, 556 full texts were scanned, and 141 articles reviewed by two independent reviewers (from a panel of paediatricians, paediatric psychologists & psychiatrists, and social workers), using standardised critical appraisal methods. Included: age <6 years, observed features in child or child -carer interaction, neglect or emotional abuse confirmed by explicit criteria. Excluded: longterm outcome data, mixed abuse/neglect where neglect could not be separated. Results: 34 studies met the inclusion criteria, 23 case control, 9 cohort and 2 case series. Case control studies matched for socio-economic, educational, ethnic aspects. Key features in the child included aggression (9 studies, 537 neglect/emotional abuse N/EA, 238 controls C) exhibited as angry, disruptive, oppositional behaviour, conduct problems, and low ego control; Being withdrawn/passive (12 studies, 664 N/EA, 279 C) reflected in negative self esteem, anxious/avoidant behaviour, passivity, less emotional knowledge, difficulties in interpreting emotional expressions in others; Having developmental delay (9 studies, 545 N/EA, 177 C) particularly delayed comprehension/expressive language, cognitive function and overall DQ. Children also showed poorer peer interaction in comparison to controls (4 studies, 69 N/EA, 102 C)showing less prosocial interaction, being less likely to relieve distress in other children, tending to play alone. Distinguishing features observed in the childcarer interaction included: hostility from mother (5 studies, 409 N/EA, 123 C), showing less verbal interactions, more punishment & criticism, less positive verbalisation. Unavailability and lack of attunement (8 studies, 368 N/EA, 111 C) carers being less responsive, more likely to end/less likely to initiate interaction, less eye contact and have developmentally inappropriate interaction. Conclusions: From early infancy there are clearly identifiable features in neglected/emotionally abused infants and toddlers, and abnormal carer- child interactions, which can be used to recognise children that need full evaluation, and early family interventions.